Growth of bio sensor materials by physical vapor transport method - Singh N.B.; Su C.H.; Arnold B.; Cullum B.; Choa F.-S.; Carpenter T.; Sachs D.; Mandal K.D. (My University, 2025)
Recently there is a big thrust on bio-inspired sensors and there has been a large rise in the investment and expectations for nanotechnology to meet these goals. For in situ sensor development materials deposition on substrate is essential part of device development. Physical vapor deposition (PVD), chemical vapor deposition (CVD) and molecular organic vapor deposition methods have developed for growth of semiconductor bulk and thin film growth with some modifications have been used for these materials. Oxides and other elements of VI group such as sulfides and selenides are key components in skins of many species. Growth of ordered structures containing these elements have been achieved by using PVD method. This paper describes effect of growth parameters during PVD growth on the quality of materials. Growth kinetics and mechanism will be discussed for the vertical and horizontal growth reactors. Since most of the efficient materials systems are multinary and in many cases noncongruent, PVD provides pathway to grow materials below melting temperature. © 2018 SPIE.